The Main Water Resources of The Republic of Moldova - Ion VASILEAN; Daniela Cristina IBĂNESCU; Adina Cătălina POPESCU (ACROSS)
The Republic of Moldova has a small area and no direct access to the sea or ocean, so its water resources are limited and are represented by surface and underground waters. However, it has an access point to the Danube River on a 430-meter stretch, at the country's southernmost point (Giurgiulești village), which offers potential access to the Black Sea. The country’s main sources of water include rivers, lakes, and groundwater. 3,621 rivers and streams represent surface waters with a total length of approximately 16,000 km and 4,261 natural lakes and artificial basins. Underground water is represented by over 7,000 artesian wells and about 179,574 wells fed from the water table. It should be noted that, in recent years, the Republic of Moldova has faced a series of problems related to water quality, including the pollution of rivers and lakes. In this sense, a more effective management of water resources is needed to ensure an adequate and sustainable drinking water supply.